Interação dinâmica pessoa-estrutura de passarelas em material compósito - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
In traditional dynamic analysis of footbridges the pedestrians are considered as moving time varying loads in vertical and horizontal directions. This approach is appropriate for most footbridges systems but for lightweight structures such as composite footbridges a high degree of human structure interaction may be expected. The analysis of the pedestrian structure dynamic interaction is performed in this work with the aid of one degree of freedom biodynamic models extracted from the literature applicable to standing person or to walking person on a rigid surface. After expressing the interaction forces the motion equations of the coupled system person structure were developed by considering one flexural bending mode of the structure as generalized coordinate. The Runge-Kutta method is employed to integrate the motion equations. Application of the model to a coupled system with standing persons subjected to free and forced vibrations yielded to the reduction of the response frequency and the growth of the apparent damping ratio as compared to the isolated structure. The Aberfeldy FRP composite footbridge was used as an example of structure which displays dynamic interaction with pedestrians. Theoretical results in terms of acceleration response were compared to the corresponding experimental measurements during the passage of a single test subject which adjusted his pacing rate to the natural frequency of the system. These comparisons showed that the interaction model provided consistent results and that good correlation depend on the biodynamic model employed.
Keywords: Material compósito; ENGENHARIAS: ENGENHARIA CIVIL